Biologic Complications of Dental Implant: An Update - Bhochhibhoya, Amar; Guragain, Manjeev; Shrestha, Rejina (Journal of Karnali Academy of Health Sciences, 2022)
With the wide use of implants to replace missing teeth, the complications of implant are also being encountered more frequently. Biologic complications are one of the complications in implant. This includes inflammation, recession, dehiscence, periimplantitis and implant failure. The dentist should be aware of these conditions and their etiology and risk factors. Relevant clinical and radiographic findings must be made for the diagnosis of the condition. The treatments should be addressed promptly. The patient must be reinforced on proper implant hygiene maintenance for the success of the implant.